Communication power - Castells, Manuel (Oxford University Press, 2011)
Drawing on a wide range of social and psychological theories, Castells presents original research on political processes and social movements. He applies this analysis to numerous recent events - the misinformation of the American public on the Iraq War, the global environmental movement to preventclimate change, the control of information in China and Russia, Barak Obama's internet-based presidential campaigns, and (in this new edition) responses to recent political and economic crises such as the Arab Spring and the Occupy movement. On the basis of these case studies he proposes a newtheory of power in the information age based on the management of communication networks.